2014
DOI: 10.1016/j.immuni.2014.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Activity Is Mediated by Monocytic Lineages Maintained by Continuous Inhibition of Extrinsic and Intrinsic Death Pathways

Abstract: Summary Non-resolving inflammation expands a heterogeneous population of myeloid suppressor cells capable of inhibiting T cell function. This heterogeneity has confounded the functional dissection of individual myeloid subpopulations and presents an obstacle for anti-tumor immunity and immunotherapy. Using genetic manipulation of cell death pathways, we found the monocytic suppressor cell subset, but not the granulocytic subset requires continuous c-FLIP expression to prevent caspase-8-dependent, RIPK3-indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
125
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 51 publications
9
125
0
2
Order By: Relevance
“…Alternatively, and according to the work by Youn and colleagues, FasL might control the process of M-MDSC conversion into G-MDSC. Furthermore, our results provide the evidence that suppression is principally found in the monocytic component of the MDSC pool, which is in line with a very recent report by Haverkamp and colleagues showing that selective loss of the G-MDSC subset did not alter tumor incidence (30). We believe, however, that the role of FasL in the MDSC compartment requires further investigations to decipher whether the impact of FasL is intrinsic or extrinsic and how it controls MDSC subset regulation in tumor-induced inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, and according to the work by Youn and colleagues, FasL might control the process of M-MDSC conversion into G-MDSC. Furthermore, our results provide the evidence that suppression is principally found in the monocytic component of the MDSC pool, which is in line with a very recent report by Haverkamp and colleagues showing that selective loss of the G-MDSC subset did not alter tumor incidence (30). We believe, however, that the role of FasL in the MDSC compartment requires further investigations to decipher whether the impact of FasL is intrinsic or extrinsic and how it controls MDSC subset regulation in tumor-induced inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…1A and B) (15,40). To characterize the functional significance of the inflammasome signaling in human mMDSCs, we modeled the human TME using …”
Section: Mdscs With Increased Inflammasome Complex Can Promote Tumor mentioning
confidence: 99%
“…MDSC viability is maintained by continuous suppression of the extrinsic caspase-8 and intrinsic mitochondrial death pathways. 5 Manipulation of either of these pathways causes a rapid decline in MDSC viability and a concomitant decrease in suppression. Therefore, we investigated whether the number and viability of transferred cells was compromised in recipient spleens posttransfer.…”
Section: Mdscs Undergo Rapid Differentiation To Cd11cmentioning
confidence: 99%
“…Recent interest in the clinical application of MDSC therapy has grown in response to basic research and a better understanding of MDSC biology; however, questions remain regarding in vivo viability, trafficking, and expansion. [3][4][5] Much like regulatory T cells (Tregs), which have shown promise in preclinical and early-phase clinical trials for GVHD, 6 MDSCs can suppress systemic immune pathology via unique mechanisms including local amino acid deprivation, nitric oxide, prostaglandin E2, antiinflammatory cytokines, reactive oxygen species, and promotion of Tregs. 7 We have shown that BM-derived cultures of MDSCs incubated with interleukin-13 (IL-13) suppress acute GVHD (aGVHD) via an arginase 1 (Arg1)-dependent depletion of L-arginine, which in turn inhibits allogenic T-cell responses.…”
Section: Introductionmentioning
confidence: 99%